2013
DOI: 10.1097/iae.0b013e31827ced51
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Topical Anesthesia and Peribulbar Anesthesia for 23-Gauge Vitrectomy Without Sedation

Abstract: Topical anesthesia without any sedation is a viable option, comparable to peribulbar block, for performing vitrectomy in selected group of patients requiring vitrectomy and thus avoiding complication of injection anesthesia and quicker postoperative recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Topical anesthesia essentially eliminates the risk of needle-related complications associated with the injection of local anesthesia. Therefore, the safety and efficacy of the topical anesthesia have been investigated for small-gauge vitrectomy, and have been demonstrated to be safe and effective [8, 9, 12, 13]. However, to best of our knowledge, no study on the safety and efficacy of the topical anesthesia for 27-gauge PPV was reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical anesthesia essentially eliminates the risk of needle-related complications associated with the injection of local anesthesia. Therefore, the safety and efficacy of the topical anesthesia have been investigated for small-gauge vitrectomy, and have been demonstrated to be safe and effective [8, 9, 12, 13]. However, to best of our knowledge, no study on the safety and efficacy of the topical anesthesia for 27-gauge PPV was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Yepez et al and Bahcecioglu et al also used operative sedation for topical anesthesia patients [6, 7, 14]. Mahajan et al used a serial topical anesthesia method, i.e., proparacaine hydrochloride drops, lignocaine gel for 1 min, another proparacaine hydrochloride infiltration with swab for 1 min [8]. Celiker et al used proparacaine hydrochloride drops 15 min preceding surgery, and then proparacaine hydrochloride infiltration with sponges for another 15 min [9].…”
Section: Discussionmentioning
confidence: 99%
“…After draping, speculum was inserted and one drop of anesthetic was administered and surgical procedure was begun. Anesthetic status was controlled by grasping the bulbar conjunctiva with colibri forceps [13]. One drop of anesthetic was applied every 30 minutes during the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Yepez et al have shown that topical anesthesia combined with neuroleptic anesthesia was also safe and effective alternative to peribulbar or retrobulbar anesthesia in posterior vitrectomy procedures with 20 G technique with scleral buckling procedures [6]. There are also reports in the literature with topical technique with 23 G technique [12, 13]. One of them reported comparison of topical anesthesia and peribulbar anesthesia for 23 G posterior vitrectomy [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation